The Use of Short Films in Teaching Listening Comprehension to Intermediate EFL Students - Norpoʻlatova Nozima Yusufxon qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article investigates the effectiveness of using short films in teaching listening comprehension to intermediate English as a Foreign Language (EFL) learners. Listening comprehension is a crucial skill for language acquisition, yet many learners struggle due to limited exposure to authentic language input and lack of engaging materials. Short films, with their combination of visual context, dialogues, and cultural content, provide meaningful, real-life language experiences that enhance comprehension, vocabulary acquisition, and motivation. The study explores practical strategies for integrating short films into the classroom, including pre-viewing activities, guided watching, post-viewing discussions, and task-based exercises. Classroom observations and learner feedback indicate that short films increase students’ attention, improve listening skills, and promote interactive learning. Pedagogical implications for EFL teachers are also discussed.